Exchange Economy from Archaic Times to the Present and Practices from Example Countries - Mehmet Şükrü Nar (Journal of Economy Culture and Society)
Trade refers to an understanding of the buying and selling or exchanging of all kinds of goods and services of economic value. In other words, trading is all about the exchanging of goods and services which people do not have and which can be supplied by others. There are several ways of doing trade, such as silently, by the use of sign language, by the language of commerce (with the use of some common trade vocabulary), and by the use of money. The exchange economy, which forms the foundation of trade, is an important alternative to today’s economic systems. In recent economic debate, forms of exchange that were used in archaic societies have frequently come to the agenda. People are seeking solutions to economic crises and unemployment through the exchange economy. In fact, the exchange economy is not only an economic understanding but also a behavioral package. This is because knowing the forms of exchange of a community indeed means understanding, in many ways, the cultural structure of that community and in particular its human relations. In this sense, the exchange system both meets economic need and improves social relations, thus ensuring the continuity of the existing order. This study provides a theoretical background to the historical development of the exchange economy. At the same time, this study also describes different country and community practices, and the function of exchange culture in both social and economic terms is discussed.